Effect of thiourea on yield and nutrient uptake of coriander (Coriandrum sativum L.) varieties under normal and late sown conditions - G L Keshwa, L R Balai, (Journal of Spices and Aromatic Crops, 2011)
A field experiment was conducted on loamy sand soil at Jobner (Rajasthan) during rabi season to study the effect of thiourea on yield and nutrient uptake of coriander (Coriandrum sativum) varieties under normal and late sown conditions. The crop sown at normal sowing time (last week of October) produced significantly higher seed yield (14.2 qha-1), straw yield (23.9 qha-1) and total uptake (14.2 kgha-1) of phosphorus (P) as compared to late sown crop. The concentration of nitrogen (N) and potassium (K) in seed and straw were significantly higher under late sown condition over normal sowing. The variety RCr-435 gave higher seed and straw yield, N and K concentrations in seed and straw and total uptake of N, P and K as compared to RCr-41. Application of thiourea (1000 ppm) at vegetative and flowering stages significantly increased the seed (24.6%) and straw yields (25.8%), N (25.6% and 27.3%) and K (25.2% and 26.0%) concentrations in seed and straw and total uptake of N, P and K as compared to water sprayed control.